HDMTX-based polychemotherapy including intraventricular therapy in elderly patients with primary CNS lymphoma: a single center series. (October 2020) - Seidel, Sabine; Kowalski, Thomas; Margold, Michelle; Baraniskin, Alexander; Schroers, Roland; Martus, Peter; Schlegel, Uwe
Background: To investigate outcome and toxicity of high-dose systemic methotrexate (HDMTX)-based polychemotherapy and intracerebroventricular (ICV) chemotherapy via an Ommaya reservoir in elderly patients with primary central nervous system lymphoma (PCNSL). Methods: We performed a retrospective analysis on patients ⩾65 years with first diagnosis of PCNSL admitted to our center between January 2015 and December 2019. These patients were treated with a standardized chemotherapy protocol in case of absent contraindications for HDMTX-based chemotherapy. The protocol contained induction therapy with systemic rituximab, methotrexate and ifosfamide and consolidation treatment with systemic cytarabine (AraC) and ICV methotrexate, prednisolone and AraC. Results: Of a total of 46 patients seen in this period, 3 did not qualify for HDMTX. Thus, 43 patients were included in this analysis. Median age was 74 years (range 65–86), median Karnofsky performance score was 50 (range 20–90). Of the 43 patients, 32 (74.4%) completed treatment including ICV therapy. Complete remission/complete remission unconfirmed was achieved in 26 of 43 patients (60.5%), partial response (PR) in 3 (7%); 5 (11.6%) had progressive disease, and 3 (7.0%) died due to treatment-related complications; in the remaining 6 (14.0%) therapy could not be completed. Median progression free survival was 16 months (95% confidence interval 8–24 months) and median overall survival had not been reached after a median follow up of 23 months (range 1–52 months); the 75th percentile survival time was 12 months. No Ommaya reservoir infection was observed. Complications of ICV treatment were pericatheter leucencephalopathy in two patients and surgical scar dehiscence with cerebrospinal fluid leak in one patient. Conclusion: Toxicity of HDMTX plus ICV chemotherapy for elderly patients with PCNSL was manageable and outcome was excellent for patients treated with this protocol.